HUBUNGAN PENGETAHUAN MASYARAKAT TERHADAP COVID - 19 DENGAN PENGGUNAAN MASKER SEBAGAI PENCEGAHAN PENULARAN INFEKSI DI LINGKUNGAN III KELURAHAN PULO BRAYAN BENGKEL KECAMATAN MEDAN TIMUR - PUTRI AGUSTIAN; ANDRI YUNAFRI (JURNAL ILMIAH MAKSITEK, 2021)
COVID-19 is a respiratory infection disease with a very rapid spread and causes high mortality rates, so that on January 30,2020 WHO declared Coronavirus Disease a Public Health Emergency of International Concern. Knowledge of COVID-19 isvery important to know so that someone can take preventive measures such as wearing a mask which aims to reduce thespread of COVID-19 infection. Knowing the relationship between the knowledge of the community of Lingkungan III,Keurahan Pulo Brayan Bengkell against COVID-19 with the use of masks as a prevention of infection transmission.Analytical descriptive with cross-sectional design. The measuring instrument in this research is a validated questionnaire.Hypothesis testing using the Chi Square test. The number of respondents was 94 people. The results showed that therewere 49 people (52.1%) who had good public knowledge of COVID-19. There are 39 people (41.5%) who use good masks.People with good knowledge of COVID-19 with the action of using good masks amounted to 31 people (63.3%) with a pvalue = 0.000. There is a Correlation between public knowledge of COVID-19 and the use of masks as a prevention ofinfection transmission.